“Much important for science and truth are still preserved by the Dnipro’s banks”: Letters of Oleksandr Bodyanskyi to Viktor Petrov - Vitaliy Andryeyev; Svitlana Andryeyeva (Київські історичні студії)
The study of the epistolary of Ukrainian archaeologists today is an important component of such a promising direction of scientific research as the history of archaeology. The purpose of this study is to publish and introduce into scientific circulation the letters of Oleksandr Bodyanskyi (1916–1992) to Viktor Petrov (1893–1969), two famous Ukrainian archaeologists. The designated ego-sources illustrate the peculiarities of the communication of the nation’s intellectual leadership in the conditions of the authoritarian Soviet system. The main milestones of their personal and professional biographies are outlined against the background of an era full of contradictions and historical cataclysms. Their participation in the Dnibrobudov expedition (1927–1932) led by D. Yavornytskyi was noted. The archeographic publication of four letters from 1964–1967 from the funds of the Central State Archives of the Museum of Literature and Arts of Ukraine (Kyiv) was carried out. This source complex combines private, public and professional components. For the history of domestic archeology, the details of the researches in the territories of the Steppe Ukraine of ancient eras from the Neolithic to Kyivan Rus’ are of interest. The main attention is paid to the debatable issues of the study of Chernyakhiv archaeological culture. The common foundations in the worldview principles of O. Bodyanskyi and V. Petrov are shown — Ukrainian-centricity, love for nature, non-acceptance of any lack of freedom, a cautious attitude to current civilizational challenges (nuclear threat, etc.). The letters record the peculiarities of the scientific environment of Ukrainian archaeologists, the regularities of their practical scientific and organizational activities, internal competition and interpersonal relationships, provide evaluation judgments about the personal traits and scientific achievements of prominent domestic archaeologists, etc.